2008
DOI: 10.1016/j.vaccine.2008.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Listeria-based HPV-16 E7 vaccines limit autochthonous tumor growth in a transgenic mouse model for HPV-16 transformed tumors

Abstract: We have shown that Listeria-based cancer vaccines inhibit the growth of transplanted tumors in a transgenic mouse model of immune tolerance where HPV-16 E7 is expressed in the thyroid gland. In this study we determine whether these vaccines are able to inhibit autochthonous tumor growth in this animal model. Mice treated with Listeria vaccines expressing E7 had significantly smaller thyroid tumors than did mice treated with controls and possessed higher numbers of antigen-specific CD8+ T cells within the splee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 14 publications
1
55
0
1
Order By: Relevance
“…On the other hand, several bacterial HPV vaccines targeting E6 and E7 have been developed. Sewell et al showed that in an HPV 16 transfected mouse model, mice that were vaccinated with Listeria based anti E7 vaccine experienced a substantial reduction in tumor size (65). Interestingly, an ongoing clinical study evaluates the efficacy of neoadjuvant listeriabased HPV vaccine ADX11-001 in patients with HPV+ HNSCC stage I-IV undergoing robot-assisted surgery (NCT02002182).…”
Section: Immunotherapeutic Strategies For Hpv-induced Hnsccmentioning
confidence: 99%
“…On the other hand, several bacterial HPV vaccines targeting E6 and E7 have been developed. Sewell et al showed that in an HPV 16 transfected mouse model, mice that were vaccinated with Listeria based anti E7 vaccine experienced a substantial reduction in tumor size (65). Interestingly, an ongoing clinical study evaluates the efficacy of neoadjuvant listeriabased HPV vaccine ADX11-001 in patients with HPV+ HNSCC stage I-IV undergoing robot-assisted surgery (NCT02002182).…”
Section: Immunotherapeutic Strategies For Hpv-induced Hnsccmentioning
confidence: 99%
“…Lm-LLO-E7, and a similar recombinant vaccine that expresses E7 fused to the listerial virulence factor ActA were found to delay the appearance of thyroid tumors and slow their growth in the E6/E7 transgenic mouse. 51 Further evidence that Listeria based tumor antigen expression systems can break tolerance was provided by Bruhn et al who showed that vaccination with Listeria, expressing TAA tyrosinase-related protein (TRP-2) induced prophylactic and therapeutic protection of mice from challenge by B16 melanoma tumors expressing TRP-2.…”
Section: Preclinical Studies Of Listeria-based Vaccines In Animal Modmentioning
confidence: 99%
“…Live recombinant vaccines that express HPV E7 or E6 proteins have proven generally to stimulate strong CD4þ and CD8þ T cell responses in mice model (Lin et al, 2010). Various bacterial vectors have been explored in HPV therapeutic vaccines including Listeria monocytogenes (Sewell et al, 2008), Lactobacillus lactis (BermudezHumaran et al, 2005), Lactobacillus plantarum (CortesPerez et al, 2005) and Salmonella (Krul et al, 1996). Moreover, some effective properties make viral vectors a induces IFN-g production at before (A), 3 weeks (B) and 6 weeks (C) after challenge.…”
Section: Discussionmentioning
confidence: 99%